Penghubung Komisi Yudisial sebagai Pengawasan Perilaku Hakim Berdasarkan Kode Etik Pedoman Perilaku Hakim - Delfina Gusman Gusman; Arya Putra Rizal Pratama (UNIB Press, 2021)
Yudicial comission after regulation revision Number 18 Year 2011 increase the authorithy power Code of ethic enforcement against judge in court togehter with province Yudicial Comission liason officer. Yudicial Comission Liason establishment by law basic Yudicial Comission Regulation Number 1 Year 2017 jo revision Yudicial Comission Regulation Number 1 Year 2012 about Shaping, Formation, the rule of work Yudicial Comission liasion of regional as for acomodation Yudicial Comission job desk. Article 3 paragraf 2 so “Yudicial Comission have right to appoitment Yudicial Comission Liason in province by neccesary”. Nevertheless, article 4 Yudicial Comissione Number 1 Year 2012 about Yudicial Comission in province have function for “accomodation Yudicial Comission job desk against maintaince dignity enforcement code of ethic in law basic decision from chief of Supreme Court number No.047/KMA/SKB/IV/2009 and chief of Yudicial Comission 02/SKB/P.KY/IV/2009 to codification to Kode Etik Pedoman Perilaku Hakim (Code of ethic of Judge Behavior Guidance)